Shooting iron [large type] - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Devil's gulch western, 2024)
"From the greatest western writers of the 21st century, the thundering new adventure starring traveling gunslinger John Holt, a lawman-for-hire on a mission to serve justice across the untamed Colorado territories - one bullet at a time. One of the deadliest, crime-infested towns in Colorado Territory, Devil's Gulch needed more than a sheriff. They needed a gunslinger. So they pinned a badge on hardcase lawman John Holt. And the rest is history. . . . When the Devil Escapes As the town's new sheriff, John Holt achieved the impossible: He drove the devil out of Devil's Gulch. Corrupt, cutthroat rancher Joe Mullen--who ruled the land with an iron fist--is finally behind bars, all thanks to Sheriff Holt. But the tables are turned when Mullen manages to overturn his prison wagon and make his escape--with an army of prisoners, outlaws, and lowlifes to do his bidding. . . . All Hell Breaks Loose. It doesn't take long for the streets of Devil's Gulch to run red with blood. Again. Or for Holt to be marked for death. Again. But this time, the sheriff's up against more than a hundred men--all of them gunning for him--and his only allies are an all-too-young deputy, an all-too-angry farmer, and a wayward wagon cook. With odds this bad, Holt is sure of only one thing: when you shoot at the devil, it's best not to miss"--